Landscapes with Araucaria in South America: Evidence for a Cultural Dimension - Reis, Mauricio Sedrez Dos (2014)
South American Araucaria species include Araucaria araucana (Mol.) C. Koch (Argentina and Chile) and Araucaria angustifolia (Bert.) O. Kuntze (Brazil and Argentina). Both species produce nut-like seeds (piñones, pinhões) that have, since pre-Columbian times, formed part of the traditional diet of local societies: Kaingang (A. angustifolia) and Mapuche-Pehuenche (A. araucana). In this work, we compared and analyzed converging and diverging characteristics of these species founded on ecological and ethnobotanical evidence. We also studied the role of human groups in the construction of Araucaria forests. The methodology used was based on a bibliographical analysis that included a wide range of sources, from ecological to social sciences. Our results show that both species hold strong cultural and symbolic significance for associated human groups. The ecological characteristics of both species have favored their rapid territorial expansion since the Holocene; however, palynological, archaeological, and ethnobotanical evidence reinforces the hypothesis that the human groups involved played a key role in this process. For both societies, there are records of past and present practices related to the transport, storage, and processing of the seeds. The landscapes where A. araucana and A. angustifolia are present also reflect use patterns that hold a level of significance that goes beyond merely utilitarian purposes. For the Kaingang and the Mapuche-Pehuenche, the Araucaria forests are associated with the concept of territoriality and play a key role in determining their identity. Our approach to cultural landscapes, which considers the importance of societies in the modelling of natural landscapes, can offer new perspectives for conservation policies and action in both forests.